Chapter Public History, memorie scolastiche e formazione. Esperienze in Toscana - CARIOLI, STEFANIA (Studi e saggi, 2019)
The contribution includes the interventions at the round table of the schools which welcomed the educational initiatives linked to the "School Memoirs" (Memorie di Scuola) project - the first specific Italian experience of Public History in the educational field - and which intertwined their itineraries for the formation of historical thought with that perspective.